The Relationship between Exclusive Breastfeeding with Foods Intake and Nutritional Status of 6-to-12-Month-Old Children in Working Area of Hamadi Primary Health Care in the City Jayapura - Ribka Fransiska Youwe; Dary Dary; Rifatolistia Tampubolon; Gelora Mangalik (Journal of Tropical Pharmacy and Chemistry, 2020)
First nutritional intake supplied to newborn infants is exclusive breast milk because it contains a lot of nutrients and it is supplied for 6-month-old children without adding weaning foods. Global Nutrition Report (GNR) report in 2014 stated that Indonesia was included in 117 countries that had three highest nutritional problems in children, namely stunting (37.2%), wasting (12.1%), and overweight (11.9%). The result of Riskesdas prevalence in 2013 regarding to nutritional status of children in Papua Province was undernutrition (21.9%) while in Jayapura there were malnutrition (3.4%) for toddlers and undernutrition (17.8%). The purpose of the research was to analyze the relationship between exclusive breastfeeding with foods intake and nutritional status of 6-to-12-month-old children in the working area of Hamadi Primary Health Care in the city of Jayapura. Quantitative research methods with cross sectional study design using the spearman rank test were done which exclusive breastfeeding as independent variable, food intake and nutritional status as dependent variables. Statistical test results showed that there was no relationship between exclusive breastfeeding and nutritional status with parameter p = 0.658, there was no relationship between exclusive breastfeeding and food intake (TKE p = 0.335), (TKP p = 0.626), (TKL p = 0.715), (TKK p = 0.980), there was a relationship between food intake and nutritional status (TKE p = 0.050), (TKP p = 0.041), (TKL p = 0.032), (TKK p = 0.049). The conclusion of this research is either exclusive or non-exclusive breastfeeding children have the same nutritional status and food intake, while children's food intake affects nutritional status of children.